Evaluation of Fucose Level and Other Parameters in Sera of Diabetic ( type II ) - shaker, L.; kassim, Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research included clinical biochemical study of some important biochemical variations of diabetes patients of type II ( NIDDM ) in comparison with the normal serum of healthy persons (control group ) , aiming to explain the relation between these variations . The following tests were done :FBS,HbA1cTF, LAF Lipid profiles ,Cu, Zn , and Cu/Zn ratio. The results have been constructed by studying the values of the relation between the variations . The relation between TF, LAF, FBS, HbA1c, Cu and CU/ Zn ratio is positive , while the relation between the above mentioned variations and Zn is negative .for the diabetes patients type (NIDDM) in comparison with healthy persons